The Europe 2020 strategy at midterm: Disappointing assessment calls for an urgent change driven by long run priorities - Karl Aiginger (WWWforEurope, 2014)
Europe 2020 tried to overcome the failures of the Lisbon Strategy. Goals set by the European commission were allowed to be adapted to take account of the starting position and the preferences of member countries ("national ownership"), the monitoring process was improved and the coordination between different policy strands institutionalized (in the European Semester), and "flagship initiatives" were aimed at initiating processes to support the strategy goals. Nevertheless halfway to the year 2020 the most important goals - the employment ratio, the reduction of poverty and research expenditure - seem to be out of reach. For the education goals the quantitative targets could be reached, but quality goals should also be monitored. The sustainability goals maybe attained because of the crisis driven stagnation in economic activity, but were set without ambition and they do not lead to a fair European contribution to limiting global warming to two degrees as envisaged in the "Energy Roadmap 2050". Neither can it be said that Europe sufficiently inverts becoming the world leader in clean technology or energy efficiency. We analyze the reasons for this underperformance and we address what urgent changes could help Europe come closer to achieving its targets by 2020. Finally we consider how economic policy should be shaped by a longer run vision of Europe's position in the globalized world of 2050 as put forward in the WWWforEurope project by a team of 34 European research groups and funded by the European Commission.
Keywords: E02; E61; H12; I13; O44; O52; 330; Economic Policy; Beyond GDP; Europe 2020 Strategy